Pengaruh Penggunaan Media Pembelajaran Wordwall untuk Meningkatkan Minat Belajar dan Berpikir Sejarah Peserta Didik di SMA Negeri 7 Bandung - Syarief, Thalia Natasya; Tarunasena, Tarunasena; Kurniawati, Yeni (Universitas Hamzanwadi, 2025)
History learning is one of the subjects that students are less interested in because it discusses space and time in the past. With the lack of interest in learning history affects the historical thinking of students which can be seen from the low learning outcomes, so there needs to be an update and present interactive learning media that makes students better understand the historical values taught. The main purpose of this research is to see the effect of wordwall learning media on students' interest in learning and historical thinking at SMA Negeri 7 Bandung. This research uses a quantitative approach with a quasi experiment research design in the form of a non-equivalent pretest-posttest control group. The population in this study were all students at SMA Negeri 7 Bandung. The sample in this study were all students of class XI A as an experimental class who were given treatment in the form of the influence of wordwall learning media and XI D who were given treatment in the form of the influence of powerpoint media. The data collection techniques used were questionnaires and pre-test-posttest test questions. The results of the study showed that after being given treatment, a visible increase was obtained from the results of statistical analysis using a paired sample t-test, showing that the significance value (Sig. 2-tailed) for historical thinking ability and learning interest was 0.000 <0.05, respectively. So H0 was rejected and Ha was accepted, meaning there was a difference in the influence of students' historical thinking ability and learning interest between before and after being given treatment using WordWall learning media.